„The smartphone is my hope“ - Muhammed Emin Kizilkaya 1994- (2021)
This exploratory qualitative research attempts to dig into a new scientific standpoint of virtual communication, mobilisation and transnationalism practised in the social media by Icelandic refugees and asylum seekers who have been travelling thousands of kilometres away from their home countries to seek refuge in Iceland, which is a sparsely populated island that is located far away from other European borders. The rational choices of travelling to Iceland is explored through the means and modes of socio-virtual tendencies, how information through the social media determine the choice of travelling to Iceland through expectations generated by commercialised tourist media platforms, what expectations the refugees and asylum seekers have on Iceland prior to their arrival, and what kind of reality that they are living in the country. This research emphasises on the hermeneutical approach through various types of qualitative methods combining micro causalities between rational choices and virtual behaviour to understand the rationale of asylum seekers targeting a country like Iceland. This research aims to be exploratory and proposes new kind of methodological approaches through socio-virtual science based on the reflection of existing methodological and ethical guidelines and through the encouragement of innovation in social sciences today.